Spontaneous polarisation of ferroelectric BaTiO3/ZnO heterostructures with enhanced performance in a Fenton-like catalytic reaction. Issue 2 (15th January 2022) - Wang, Yan; Liu, Liangliang; Zhao, Weixing; Ma, Rong; Pang, Jiaojiao; Hu, Dengwei; Dou, Zhen; Song, Meng; Li, Tong; Miao, Kangkang
Abstract: Ferroelectric BaTiO3 /ZnO heterojunction catalysts synthesised via the sol–gel method present obvious enhancements in spontaneous polarisation-driven Fenton-like catalytic activity. In this study, the oxidative decomposition of methylene blue (MB) dye was used as a model reaction. Pure BaTiO3 -activated potassium monopersulphate (PMS) could decompose up to 48% of MB dye in an aqueous solution after 40 min. MB degradation rate firstly increased and then decreased as the ZnO content of the ferroelectric BaTiO3 /ZnO heterojunction materials was increased. The maximum degradation rate of 100% and good cycling stability were observed when the BaTiO3 :ZnO molar ratio was 1:1. Three active species, namely, holes (h + ), sulphate radicals (SO4 − ) and hydroxyl radicals (OH ), were produced following the spontaneous polarisation-driven catalytic degradation of the dye. Amongst these species, h + and SO4 − were the main active species. Enhancements in the Fenton-like catalytic activity of BaTiO3 /ZnO may be attributed to the formation of semiconductor heterojunctions, which could improve the spontaneous polarisation strength of ferroelectric BaTiO3, promote the effective separation of e − –h + pairs and accelerate PMS activation. In summary, a novel PMS activation method was developed to provide a nontoxic, efficient and environmentally friendly technology for the degradation of organic pollutants.